The Landing of CMS Missionaries to an Ottoman Dominion: Missionary Education in Egypt (1825-1862) - DEMİRKIRAN, ARZU MERYEM (EDAM, 2016)
During the period under investigation (1825-1862), Egypt was a dominion of the Ottoman Empire and attracted the attention and interest of all European states that had been displaying their military and commercial superiority for a long time. In the nineteenth century, Egypt was not only destitute of schools, but had also entered a rapid modernization process since the reign of Mehmet Ali Pasha. This had created an extremely favourable environment for missionary activities in Egypt from the beginning of the nineteenth century. From its findings, this research will attempt to put forth that the missionary schools opened by the Church Missionary Society (CMS) in fact reflected the encouragement of Egyptian Rulers to persons who wished to introduce European institutions. In this respect, the activities of the Protestant societies were not only important for improving the political, economic and commercial interests of England in the region, but also for creating an awareness in Egypt that the most important issues for protecting national existence were raising the level of education and providing cultural development.
Keywords: The Church Missionary Society; Ottoman Empire; Cairo; Missionary education; Boys' school; Girls' school